Sentiment Analysis on Islamic Insurance in Indonesia - Aam (SMART Insight, 2022)
This research was conducted to review Islamic insurance within the scope of sharia economics both in terms of scientific research in the form of published journals and the sentiments of the Indonesian people in response to the development of Islamic insurance. The method used is descriptive bibliometric statistical analysis and sentiment analysis from secondary data in the form of more than 50 published papers in the past 5 years and primary data in the form of more than 100 questionnaire respondents from Jabodetabek area which are then processed using VOSViewer and SentiStrength. The results showed that the bibliometric mapping was divided into 5 clusters; cluster 1 consists of 6 topics, cluster 2 consists of 6 topics, cluster 3 consists of 5 topics, cluster 4 consists of 4 topics and cluster 5 consists of 3 topics. The results of the sentiment analysis show good sentiment (positive) by 24%, bad sentiment (negative) by 14% and the rest have neutral sentiment (neutral) 62%. This study is the first comprehensive study to discuss the sentiment analysis of the Islamic insurance theme with primary and secondary data.